2017
DOI: 10.21474/ijar01/5202
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Prevalence and Seasonal Variation of Diarrheal Diseases Among Under-Five Children of Jhansi, Uttar Pradesh, India.

Abstract: Background: Diarrheal disease forms one of the two major killer diseases in children under five years of age in the developing world. Data on the prevalence and related factors of diarrhea in Bundelkhand region is quite scanty. A community-based cross sectional study was undertaken among 301 under-five children of field practice area Medical College Jhansi during 2015-16, to find out the burden of diarrheal diseases and the effect of seasonal variation on the pattern of diarrheal diseases. Methods: Cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The proportion of households that reported diarrheal diseases was higher during the dry season than during the rainy season. The higher prevalence of diarrheal disease during the dry season was in agreement with previous studies conducted in varying socio-cultural settings [4,[6][7][8]. In another study, a bimodal distribution of the peak period of diarrheal disease was observed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The proportion of households that reported diarrheal diseases was higher during the dry season than during the rainy season. The higher prevalence of diarrheal disease during the dry season was in agreement with previous studies conducted in varying socio-cultural settings [4,[6][7][8]. In another study, a bimodal distribution of the peak period of diarrheal disease was observed.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated the possibility of seasonal variations in some components of household water security like accessibility and water quality [4][5][6]. The burden of diarrheal disease has also been shown to vary across seasons in some studies with a peak during the dry season [4,[6][7][8] while a bimodal pattern was observed in a study conducted among under-5 children in Ghana [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation